Demokrasi, Politik dan Kepemimpinan di Indonesia Dalam Analisis Bibliometrik - P. Manohara, Brigita; Sartika, Ika (Journal of Accounting and Finance Management, 2025)
This research analyzes the dynamics of democracy, politics, and leadership in Indonesia through a bibliometric approach. The main objective is to identify publication trends, interauthor linkage maps, and thematic patterns using the Vosviewer application. Data were obtained through a systematic search on Google Scholar with specific keyword restrictions and open access. The analysis showed a significant decline in related publications since 2020, influenced by the shift in academic focus during the COVID-19 pandemic. Themes such as politics, political systems and democracy remain dominant, with social media playing a strategic role in the transformation of political communication, despite presenting challenges in the form of disinformation. The author-toauthor linkage map identified 416 clusters with low levels of collaboration, highlighting the need to strengthen research networks across sectors. Keyword analysis also found research gaps related to political governance innovation and inclusive democracy. This research emphasizes the importance of academic collaboration to address the complexity of strategic issues and recommends an interdisciplinary approach as a solution.